2009
DOI: 10.1111/j.1460-9568.2009.06621.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulus–response compatibility on inhibitory processes in Parkinson’s disease

Abstract: Parkinson's disease (PD) is a neurodegenerative basal ganglia disorder accompanied by deficits in cognitive functions. One important executive function is the inhibition of responses. Due to basal ganglia damage, processes related to the selection of response are also dysfunctional. However, the relevance of deficits in response selection to processes related to response inhibition in PD is not clear. In this study we examined these processes by means of event-related potentials (ERPs) in two Go/Nogo tasks. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 38 publications
2
52
0
Order By: Relevance
“…Due to the usually large proportions of Go-trials, the participants develop a predominant tendency to respond that places high demands on executive processes of action restraint on NoGo-trials (Eigsti et al, 2006;Lange et al, 2014;Lange and Eggert, 2015). As displayed in Table 3, NoGo-P3 amplitudes were repeatedly reported to be attenuated in PD patients (Beste et al, 2009a;Bokura et al, 2005;Osawa et al, 2005;Pulvermüller et al, 1996; but see Beste et al, 2010). Note that Beste et al…”
Section: Nogo Erps: Response Conflict and Inhibitionmentioning
confidence: 88%
“…Due to the usually large proportions of Go-trials, the participants develop a predominant tendency to respond that places high demands on executive processes of action restraint on NoGo-trials (Eigsti et al, 2006;Lange et al, 2014;Lange and Eggert, 2015). As displayed in Table 3, NoGo-P3 amplitudes were repeatedly reported to be attenuated in PD patients (Beste et al, 2009a;Bokura et al, 2005;Osawa et al, 2005;Pulvermüller et al, 1996; but see Beste et al, 2010). Note that Beste et al…”
Section: Nogo Erps: Response Conflict and Inhibitionmentioning
confidence: 88%
“…The earlier of the two components is the Nogo-N2, a negative component that is thought to reflect either pre-motor inhibition [32] or monitoring of response conflict [34]. The later of the two components is the Nogo-P3, a positive deflection that has been linked to the evaluation of successful inhibition, given that it peaks too late after the response to directly reflect inhibition processes [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Action selection processes, which become increasingly important once stimulus identification processes are finished, are most likely reflected by another ERP, the N2 ERP-component (e.g., Beste et al 2008aBeste et al , 2009aBeste et al , 2010bGajewski et al 2008;Van Veen and Carter 2002;Willemssen et al 2009). WildWall et al (2008) showed that the N2 is usually small when stimulus-response mapping is easy, while it is enhanced when response selection is intensified due to a conflict occurring between intended and not intended responses (Folstein and Van Petten 2008;Van Veen and Carter 2002).…”
Section: Introductionmentioning
confidence: 99%